Perceptions of Social Networks Impact on Countering Violent Extremism Among University Students - Mohammad Alhumsi (Arab Journal for Security Studies, 2023)
This study aims to investigate the perceptions of Saudi students at the Saudi Electronic University regarding the impacts of social networks on countering violent extremism and their relationship with variables such as gender, academic year, and type of college. The sample for this study comprised 110 male and female students at the Saudi Electronic University. To collect data, a cross-sectional questionnaire was used and distributed to the research participants. Descriptive statistics, an independent sample t-test, and one-way analysis of variance (ANOVA) were employed to analyze the data. This research revealed that social networks, including platforms like Facebook, Twitter, YouTube, and others, encompass thoughts and beliefs that highlight positive impacts on countering violent extremism. However, they also include misleading thoughts and beliefs that emphasize negative impacts, promoting violent extremism. This implies the efficient role social networks play in the life of individuals. Moreover, the findings revealed that there were no statistically significant differences among Saudi Electronic University students in their perceptions of the impact of social networks on countering violent extremism, based on the variables of academic year, type of college, and gender. Given the rapid growth of technology as well as the acceleration of online activities, the study recommends increasing community awareness on how to Seleguard gaist in Social networks.